First Experimental Iron Process Based on The Montalat Iron Sites in Central Kalimantan – Indonesia - Sofian, Harry Octavianus; Hartatik, Hartatik; Sunarningsih, Sunarningsih; Susanto, Nugroho Nur; Dhaneswara, Gauri Vidya; Sulistiyo, Restu Budi; Karyanantio, Agus (Badan Riset dan Inovasi Nasional, 2023)
This article is based on an experimental iron furnace from archaeological sites in Central Kalimantan – Indonesia, from July 2019. The iron furnace for the experiment is replicated the original iron furnaces from the latest research found in 2017 in the Benangin and Temelalo sites from Central Kalimantan, Indonesia. The experiment aims to prove whether the iron furnace can melt metal. From the archaeological experiment we can answer questions about the iron process in Central Kalimantan in the past with the local resource’s laterite and hematite. From archaeological experiments, duplicate iron furnaces can make iron raw materials into melts and extract iron from hematite and laterite raw materials. The results showed that the ancient people in Central Kalimantan were able to make iron from raw materials and process it as iron ingot.